Learner differences in theory and practice†. Issue 1 (1st January 2016) - Kalantzis, Mary; Cope, Bill
ABSTRACT: This paper explores the complex and shifting dimensions of the social, cultural and bodily differences that impact on learners and their learning. Our theoretical argument proceeds in five stages. First, we build a typology of terms used to classify demographic differences for the purposes of designing, implementing and evaluating the effectiveness of educational institutions and programs: material conditions (social class, locale and family); corporeal attributes (age, race, sex and sexuality, physical and mental abilities); and symbolic representations (language, ethnos, communities of commitment and gendre). Second, we address the paradigms of civic association that modern nation-states have used to negotiate these differences: exclusion, assimilation and an aspirational regime that we call 'civic pluralism'. Third, we explore complications that render the demographic categorizations problematic. Fourth, we propose an alternative and supplementary frame for social and learner differences based on 'lifeworld differences'. Finally, we explore the ways in which civic pluralism might be translated into educational practice. We interleave these theoretical explorations with an analysis developed for an evaluation of an inclusive education program in Roma communities in Northern Greece. The Roma serve as a case study of the complex ways in which categories of difference play out in social and educational reality.